Rehabilitation after arthroscopic decompression for femoroacetabular impingement - Enseki, K. R.; Martin, R. R.; Kelly, B. T. (Clinics in Sports Medicine, 2010)
The use of arthroscopic technology to address pathologic conditions of the hip joint has become a topic of growing interest in the orthopedic community. Addressing femoroacetabular impingement through this method has generated additional attention. As surgical options evolve, rehabilitation protocols must meet the challenge of providing a safe avenue of recovery, yet meeting the goal of returning to high levels of functioning. Current rehabilitation concepts should be based on the growing body of evidence, knowledge of tissue healing properties, and clinical experience.